Physiological condition of trees and shrubs under arid conditions of the foothill zone in the South-East of Kazakhstan depending on the applied technologies moisture protection (Experimental biology, 2020)
This article describes the water regime of 11 trees and shrubs species in the foothill zone of the south-east of Kazakhstan. In the research results identified some species: Malus domestica cv. ‘Saltanat’, Ribes nigrum L. cv. ‘Minai Shmyrev’, Thuja occidentalis L.,  Tilia cordata Mill., Berberis iliensis M. Pop., Padus racemosa (Lam.) Gilib., Crataegus oxyacantha L., that have high moisture supported ability and general water content.The applied technologies of moisture supply specifically affect each of the test crops and suggest a good adaptability of the ornamental-shrub plants. Hydrogel "Aquasorbs" is an effective means of regulating the water-holding capacity of the soil.A comparative analysis of the physiological processes of the water regime of plants between different water-saving technologies showed that the use of the moisture-absorbing polymer "Aquasorbs" is most effective at a dose of 1.0 kg/m3. Also, good results were obtained in the variant - furrow irrigation, which is a control.The purpose of the research was the scientific substantiation and development of methods for the use of polymer hydrogel "Aquasorbs" to improve the water-physical properties of the soil, which will contribute to the development of consumer and ornamental horticulture in the arid regions of South-East Kazakhstan.Key words: hydrogel, Aquasorbs, trees and shrubs, variant, climate, water holding capacity, total water content.